Saperi mobili: Un’etnografia ibrida dell’emergenza abitativa post-sisma a Port-au-Prince - Salome, Giovanna (Antropologia Pubblica, 2024)
Post-disaster settings represent thick and slippery ethnographic contexts within which the anthropologist is constantly called to redefine the analytical and methodological tools used for the interpretative work, and renegotiate the legitimacy of his/her own being there and the knowledge learned over the course of the study. That appears especially urgent when the researcher takes the risk to juxtapose the roles of «expert» and «witness» as it happened over the course of my fieldwork on post-disaster housing emergency in Haiti. Beginning from these premises, I will try to connect the evolution of my positioning on the field - in terms of professionals roles assumed and analytical perspectives adopted - with the construction/deconstruction process of my object of investigation. The description of my research procedure will therefore represent a tool for reflecting critically on challenges, advantages and contradictions conveyed from an applicative use of the anthropological knowledge in contexts of crisis.